2014
DOI: 10.1155/2014/641959
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Phytase Treatment on Phosphate Availability in the Potential Food Supplement Corn Distillers’ Grains with Solubles

Abstract: The most effective treatment of the potential food supplement corn distillers’ grains with solubles using a fungal phytase to degrade phytic acid and release phosphorus was explored. Compared to the untreated grains with solubles, the phytic acid level in the grains with solubles was reduced by phytase treatment but treatment with 4 units of enzyme/g was more effective than 2 units of enzyme/g after 2 h. At 30°C or 45°C, 4 units of phytase/g reduced the phytic acid content of the grains with solubles by at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…and S. cerevisiae have been previously reported (Olukomaiya et al 2020;Onipede et al 2020). It is widely acknowledged that decomposition of phytic acid increases the availability of many cations and thus nutritional value (West 2014;Gupta et al 2015). Also, the enzymatic degradation of phytic acid by phytase enzyme requires an optimum pH which can be provided by natural fermentation (Gupta et al 2015).…”
Section: Chemical Composition Of Rsm and Fsmmentioning
confidence: 99%
“…and S. cerevisiae have been previously reported (Olukomaiya et al 2020;Onipede et al 2020). It is widely acknowledged that decomposition of phytic acid increases the availability of many cations and thus nutritional value (West 2014;Gupta et al 2015). Also, the enzymatic degradation of phytic acid by phytase enzyme requires an optimum pH which can be provided by natural fermentation (Gupta et al 2015).…”
Section: Chemical Composition Of Rsm and Fsmmentioning
confidence: 99%
“…(Taheri et al 2009;Garc ıa-Mantrana et al 2016;Priyodip et al 2017) and SC (Kłosowski et al 2018) which have been previously reported. It is widely acknowledged that decomposition of phytic acid, increases the availability of many cations and followed by nutritional value (West 2014;Gupta et al 2015).…”
Section: Nutrient Digestibility and Digestive Enzyme Activitiesmentioning
confidence: 99%